1997
DOI: 10.1093/carcin/18.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Apc and the entire chromosome 18 but absence of mutations at the Ras and Tp53 genes in intestinal tumors from Apc1638N, a mouse model for Apc-driven carcinogenesis

Abstract: The Apc1638N mouse carries a targeted mutant allele at the endogenous adenomatous polyposis coli (Apc) gene and represents a unique in vivo model to study intestinal tumor formation and progression. Heterozygous Apc+/Apc1638N mice progressively develop 5-6 adenomas and adenocarcinomas of the small intestine within the first 6 months of life following a histologic sequence similar to that observed in human intestinal tumors. Here, we present the somatic mutation analysis of a total of 57 tumors. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 12 publications
5
77
0
Order By: Relevance
“…In each case, it is well documented that loss or inactivation of the wild-type allele elevates Wnt signaling and initiates intestinal adenoma formation (Levy et al, 1994;Smits et al, 1997). As assayed by replicate quantitative real-time PCR (qRT-PCR) for each tumor for each marker, there was great heterogeneity in Jagged1 expression in the tumors relative to the low levels in the flat mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…In each case, it is well documented that loss or inactivation of the wild-type allele elevates Wnt signaling and initiates intestinal adenoma formation (Levy et al, 1994;Smits et al, 1997). As assayed by replicate quantitative real-time PCR (qRT-PCR) for each tumor for each marker, there was great heterogeneity in Jagged1 expression in the tumors relative to the low levels in the flat mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…One approach was to examine the tumors from Apc mutant mice for mutations in these genes and the second is the generation of mice with mutations in some of these genes and mate them with the Apc mutant mice and ascertain their in¯uence on tumor susceptibility. When the GI tumors from Apc mutant mice were examined, the only consistent alteration that was observed is the loss of the wild-type copy of the Apc allele through nondisjunction (Figure 1) (Smits et al, 1997;Luongo et al, 1994). These results indicated that the earliest genetic change during tumor progression is the loss of the wild-type Apc allele and this loss is su cient for progression of the tumor to the adenoma stage.…”
Section: Genetic Basis For Colorectal Cancermentioning
confidence: 90%
“…These results indicated that the earliest genetic change during tumor progression is the loss of the wild-type Apc allele and this loss is su cient for progression of the tumor to the adenoma stage. GI tumors of Apc were also examined for K-ras mutations, but no mutations were found (Smits et al, 1997;Shoemaker et al, 1997).…”
Section: Genetic Basis For Colorectal Cancermentioning
confidence: 99%
“…To create a model system to study the e ects of Mlh1 de®ciency in intestinal tumorigenesis, we previously crossed Mlh1 7/7 mice with the Apc 1638N strain which carries a heterozygous germline mutation in Apc. Apc 1638N mice typically develop three to ®ve intestinal tumors per animal within 9 months, and 475% of these display allelic loss of the wild-type Apc allele (Yang et al, 1997;Smits et al, 1997). Compared to other Apc mutant strains, such as Apc Min and Apc D716 (Moser et al, 1990;Su et al, 1992;Oshima et al, 1995), Apc 1638N displays a relatively mild phenotype and is longer lived.…”
Section: Introductionmentioning
confidence: 99%